Formulation and Evaluation of Anti-Acne Lotion Containing Red Ginger (Zingiber officinalle Roscoe) Essential Oil - Dwi Indriati; Ike Y. Wiendarlina; Annisa S. Carolina (Pharmacology and Clinical Pharmacy Research)
Red ginger (Zingiber officinalle Roscoe) has been empirically used as antibacterial agent. This study was aimed to formulate anti-acne lotion containing red ginger essential oil and to evaluate its antibacterial activity against Propionibacterium acnes and Staphylococcus epidermidis. Extraction and distillation of 10 kg of red gingers were performed to obtain its essential oils. The lotions were prepared using oil in water (o/w) base with various concentration of red ginger essential oils, i.e., 2.5%, 5%, and 7.5%. The lotion was assayed to determine organoleptic, homogeneity, pH, viscosity, and irritation-inducing level. Antibacterial activity test was conducted using disk-difussion method. Results indicated that the 7.5% concentration exerted the strongest activity in inhibiting P. acnes (inhibition zone 12.4 mm) and S. epidermidis (inhibition zone 29 mm). In conclusion, anti-acne lotion containing 7.5% of red ginger essential oil was effective to control acne inducing bacteria and fulfilled the required standards.Keywords: Red ginger, essential oil, anti-acne, Propionibacterium acnes, Staphylococcus epidermidis